Representação da informação arquivística: uma proposta para o Arquivo Histórico Waldemar Duarte - Dantas, Célia Medeiros (2015)
Information is one of the society´s inputs and it highlights an increasing concern as to its retrieval, organization, storage and availability. Taking into account this reality, the current piece of research is motivated by the information representation in documents of permanent character on the web, once the information in this medium enables the information retrieval regardless of time and space, with the archivist´s participation as a mediator of information. For this reason, this piece of research was derived from the perception of the relevance of the colonial period documentation stored in the Waldemar Duarte Historical Archive belonging to the Cultural Space Foundation of Paraíba (FUNESC). In this sense, this study aims to identify a metadata pattern for the descriptive representation of the information of this documentation. It intends, specifically, to describe the historical context of the Waldemar Duarte Historical Archive and it identifies the procedures that represent this archive as well as it highlights the representative elements in both the Information Science and the Archival Science. Hence, this piece of research has empirical classification, with qualitative and quantitative approach, descriptive category, having the observation as tool for data collection so as to analyze the behavior of the historical archive´s users and collaborators as well as the documental analysis based on the research of 78 documents related to the Colonial Period in order to adapt the pattern to this sample. The purpose of this research is given in two main aspects: Descriptive Representation of Information and the Thematic Representation of Information. In the Descriptive Representation of Information, a metadata pattern was delimited based on the analysis of three patterns, being two archival patterns. The analysis of the patterns occurred due to the exclusion of common metadata, the comparison of metadata with the data found in the Colonial Period documentation and which pattern presents major coverage for the descriptive representation for the documents of permanent character. For the proposal of the Thematic Representation of Information, aspects that define the creation of indexation mechanisms, indexing policies, controlled vocabulary and abstracts were established for the Colonial Period documentation. Thus, the need for public powers is perceived while producing initiatives for the dissemination of their archives in a virtual environment favoring thus the emergence of new studies. The definition of a metadata pattern will contribute to the representation of documents from the Brazilian Colonial Period; this can be expanded for the documentation of the other historical periods stored in the Waldemar Duarte Historical Archive.